Leadership gold : lessons learned from a lifetime of leading - Maxwell, John C., 1947- Maxwell, John C. (Nashville : Thomas Nelson, 2008)
"Learning to lead effectively"--Provided by publisher.
Includes bibliographical references (p. 255-256).
Keywords: Leadership; Industrial management